Prevalence and molecular characterization of human bocavirus-1 in children and adults with influenza-like illness from Kunming, Southwest China - Yanhong Sun; Lili Jiang; Yaoyao Chen; Zhaosheng Liu; Meiling Zhang; Xiaonan Zhao; Xiaoyu Han; Lifen Zhang; Xiaoqing Fu; Jienan Zhou (Microbiology Spectrum)
ABSTRACT Human bocavirus-1 (HBoV-1) has been associated with respiratory infections in both children and adults, often presenting symptoms similar to those of influenza. Understanding the prevalence and molecular characteristics of HBoV-1 in individuals with influenza-like illness (ILI) is essential for enhancing the diagnosis and treatment of respiratory infections in Kunming, Southwest China. Between December 2017 and December 2023, demographic and clinical data, along with respiratory tract specimens from individuals aged 0 to 97 years with ILI, were collected at three sentinel hospitals in Kunming. Each specimen was tested for 18 respiratory viruses, and the positive rates of HBoV-1 across different age groups were analyzed. Amplification of the near-complete HBoV genome was achieved through three overlapping fragments, followed by next-generation sequencing (NGS) and phylogenetic analysis. A total of 20,181 respiratory samples were collected from patients aged 1 month to 97 years presenting with ILI symptoms between December 2017 and December 2023, with HBoV detected in 0.8% of the samples. The prevalence was 1.0% (165/16,406) in children and 0.1% (3/3,775) in adults, with a significantly higher detection rate in pediatric patients (<18 years old) compared to adults (≥18 years old) (P < 0.001). Among the 168 HBoV-positive participants, 165 (98.2%) were children under 18 years, while 3 (1.8%) were adults. Genome-wide phylogenetic analyses indicated that HBoV-1 was the predominant genotype, showing that the HBoV-1 strains circulating in Kunming are closely related to strains from other regions of China and globally. Our findings confirm the prevalence of HBoV-1 in individuals with ILI in Kunming and provide valuable insights into the molecular characteristics of HBoV-1 in this region. Further studies are necessary to explore the clinical implications of HBoV-1 infection and its role in respiratory illnesses.IMPORTANCEViral respiratory infections are a leading cause of morbidity- and mortality-associated influenza-like illness (ILI) cases. It is estimated that there are several billion cases of ILI globally each year. Monitoring data from China in 2023 indicate that there are approximately 17 million cases of ILI nationwide. In the United States, the annual incidence of ILI ranges from 9 to 49 million cases. Human bocavirus-1 (HBoV-1) has been identified as a causative agent of ILI. The global prevalence of HBoV-1 respiratory infections varies from 1% to 56.8%, with the majority of studies focusing on pediatric populations; however, research including a broader age range is limited. Currently, the prevalence of HBoV-1 in the Kunming area is not well characterized, and its molecular features remain inadequately described. This study aims to analyze the prevalence of HBoV-1 among ILI cases in Kunming, encompassing both pediatric and adult patients. We present 107 complete genomic sequences of HBoV-1 strains obtained from three ILI sentinel hospitals in the region. Furthermore, we conducted phylogenetic analysis, homology comparisons, and assessments of nucleotide and amino acid substitution site variations. These findings provide important insights for further investigations into HBoV-1 and its epidemiological significance.